Beban Kerja dengan Stres Kerja Perawat dalam Pelaksanaan Asuhan Keperawatan di Ruang Rawat Inap - Fitri Andi Sabil (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the relationship between workload and work stress of nurses in implementing nursing care in inpatient rooms. The method used is a cross-sectional survey with 69 respondents. The results showed that nurses had a light workload (68.1%) and nurses who experienced light work stress (60.9%). After statistical tests were carried out, it was found that there was a relationship between workload and work stress of nurses, with a value of p = 0.018 (<0.05). In conclusion, there is a relationship between nurses' workload and work stress in the inpatient room of Luwuk Banggai Hospital. Keywords: Workload, Implementation of Nursing Care, Work Stress